Exosomal miR-126: Unveiling Its Diagnostic and Therapeutic Potential in Chronic Kidney Disease - Alzahrani, Faisal; Alzahrani , Fahad; Hosawi, Salman; Ankawi, Ghada; Alzahrani, Bader; Riza , Yasir (Journal of King Abdulaziz University: Science, 2024)
Chronic Kidney Disease (CKD) represents a significant global health challenge, with a prevalence estimated to affect 8-19% of the global population. Its pathogenesis involves complex interactions between various cellular and molecular mechanisms, among which exosomes play a pivotal role. Exosomes are small extracellular vesicles that facilitate intercellular communication by transporting biomolecules, including microRNAs (miRNAs), between cells. This review highlights the crucial function of exosomes in CKD, with a particular focus on the role of miR-126, a microRNA encapsulated within exosomes, which has shown promise both as a diagnostic biomarker and a therapeutic target for CKD. We elaborate on the nature, function, and altered expression patterns of exosomes in CKD, underscoring the diagnostic and prognostic significance of urinary exosomes. Furthermore, we delve into the regulatory role of miR-126 in vascular integrity and angiogenesis, its association with CKD progression, and its potential therapeutic implications. Our comprehensive analysis aims to illuminate the intricate mechanisms by which exosomes and miR-126 contribute to CKD pathophysiology, offering insights into their utility in developing novel diagnostic tools and therapeutic strategies. This synthesis of current research underscores the importance of further investigation into exosomal miR-126, paving the way for innovative approaches to tackle CKD.